Universal Aspects of the Genus Mucuna and the Properties Describe of Mucuna urens and Mucuna pruriens - Monge, María Celeste Ortega; Salas, María Fernanda Rojas; Chavarría-Rojas, Marianela; Berrocal, Gustavo Carazo; Redondo, German Madrigal (Pharmacognosy Reviews)
The plant genus Mucuna comes from the family Fabaceae, subfamily Papilionaceae. At present, about 100 species of climbing shrubs of the genus Mucuna have been found, among which Mucuna pruriens and Mucuna urens stand out, due to the large number of pharmacological properties they possess. We sought to exemplify some of the most important uses, as well as pharmacological and nutritional properties that have been found over the years in Mucuna urens and Mucuna pruriens. Plants of the genus Mucuna have been used in various areas worldwide because they possess a large number of phytoconstituents that give them multiple properties. These plants have stood out for their nutritional value, their antioxidant activity, and their properties to treat various pathologies.
Keywords: Antioxidants; Mucuna; Mucuna pruriens; Mucuna urens; Nutritive value; Pharmacological properties